Concentrations and Health Implications of PM2.5, PM10, and Gaseous Pollutants in Communities near Ibom Power Company, Ikot Abasi, Nigeria - Ioryue Ijah Silas; Augustine Uche Abel; Idongesit Sunday Ambrose; Akpanuko Mary Emmanuel; Abah Enuwa Bridget; Macdougal Nsikak Saddie; Ekpenyong Ofofonini Ukofia (International Journal of Applied Chemistry, 2026)
Particulate Matter (PM) exposure from ambient air has been linked to a number of ailments, and monitoring is necessary in every industrial areas or centers to identify overexposure early. This study's assessed the concentrations of PM2.5, PM10, and related gaseous pollutants in Ibom Power Company, Ikot Abasi, Nigeria, including carbon monoxide (CO), ozone (O3), and nitrogen dioxide (NO2). The concentrations of PM2.5, PM10, NO2, CO, and O3 at three chosen towns surrounding Ibom Power Company were measured using an aerosol mass monitor. The hazard quotient (HQ) of the average hourly dose (AHD) and average daily dose (ADD) exposures to the particles was calculated using the obtained values. The findings showed that, with the exception of Ikpetim, where the values (5.26±0.21 and 5.16±0.20 μg/m3) were below the permitted limits, all of the villages had PM 2.5 and PM 10 levels over the 15μg/m3 permissible range advised by the WHO. With the exception of Ikpetim, where the NO2 value was within the limit, all settlements had CO and NO2 values over the 25μg/m3 and 7μg/m3 acceptable levels, respectively. In the meantime, O3 levels were within allowable bounds (<100μg/m3) in every community. In several places, the HQ of the ADD was higher than 1, yet the HQ of the AHD of the pollutants was below the threshold of 1. The findings suggest that daily exposure to PM2.5, PM10, NO2, and CO in certain areas can have detrimental effects on residents' health. It is recommended that government agencies responsible for health and the environment develop policies aimed at reducing pollution, and power plants should not be located near residential areas, but specific areas should be designated for power plant siting.